Dietary Goji Shapes the Gut Microbiota to Prevent the Liver Injury Induced by Acute Alcohol Intake - Guo, Lin; Guan, Qijie; Duan, Wenhui; Ren, Yilin; Zhang, Xiao-Juan; Xu, Hong-Yu; Shi, Jin-Song; Wang, Fang-Zhou; Lu, Ran; Zhang, Hui-Ling; Xu, Zheng-Hong; Li, Huazhong; et al. (Frontiers in Nutrition, 2022)
Diet is a major driver of the structure and function of the gut microbiota, which influences host physiology. Alcohol abuse can induce liver disease and gut microbiota dysbiosis. Here, we aim to elucidate whether the well-known traditional health food Goji berry targets gut microbiota to prevent alcohol-induced acute liver injury. The results showed that Goji supplementation for 14 days alleviated alcohol-induced liver injury as indicated by lowering serum aspartate aminotransferase, alanine aminotransferase, pro-inflammatory cytokines as well as lipopolysaccharide content in liver tissue. Goji maintained the integrity of epithelial barrier and increased the levels of butyric acid in cecum contents. Furthermore, we established the causal relationship between gut microbiota and liver protection effects of Goji by antibiotics treatment and faecal microbiota transplantation (FMT) experiments. Both Goji and FMT-Goji increased glutathione (GSH) in the liver and selectively enriched the butyric acid-producing gut bacterium Akkermansia and Ruminococcaceae by using 16S rRNA gene sequencing. Metabolomics analysis of cecum samples revealed that Goji and its trained microbiota could regulate retinoyl β-glucuronide, vanillic acid, and increase glutamate and pyroglutamic acid which involved in GSH metabolism. Our study highlights the communication between Goji, gut microbiota, and liver homeostasis.